Nevirapine inhibits migration and invasion in dedifferentiated thyroid cancer cells - Shang, Hongxia; Zhao, Junyu; Yao, Jinming; Wang, Huanjun; Wang, Shengnan; Dong, Jianjun; Liao, Lin (Thoracic cancer, 2019)
Background Metastatic or recurrent thyroid cancer often behaves aggressively, and approximately two‐thirds of patients present with radioiodine resistance. Effective therapies to suppress thyroid cancer metastasis are urgently needed. Nevirapine has been proved to suppress tumor growth and induce differentiation in several tumor cells, but has not previously been evaluated in metastasis of thyroid cancer. The present study aimed to investigate the effect of nevirapine on migration and invasion in dedifferentiated thyroid cancer cells. Methods Human dedifferentiated thyroid cancer cell line (WRO 82‐1) was subject to real‐time quantitative PCR, western blot and transwell migration/invasion assays. The liver metastasis in tumor xenografts of nude mice was subject to hematoxylin‐eosin (HE) staining. Results Nevirapine significantly repressed cell migration and invasion in WRO 82‐1 cells, and surprisingly significantly decreased liver metastatic tumor in the nude mouse model of dedifferentiated thyroid cancer compared with that of the control. Moreover, nevirapine significantly decreased the expression of IL‐6 mRNA and phosphorylation of JAK2 (Y1007+Y1008) and STAT3 (Tyr 705) in WRO 82‐1 cells compared with those in control cells. Conclusion Our findings suggest that nevirapine significantly repressed migration and invasion/metastasis in WRO 82‐1 cells and tumor xenografts, which may be related to inhibition of IL‐6/STAT3 signaling pathway. It promises great potential as a novel therapy for thyroid cancer, especially for those patients with metastasis.